ENT 530 Social Media Portfolio: SyahFresh / Syahmi Zaini Muhammad Amirul Ridhzuan Stanny - Muhammad Amirul Ridhzuan Stanny, Syahmi Zaini (2021)
SyahFresh is an agent that offer and promote a variety flavour of Farm Fresh Milk. As for now, SyahFresh offers 6 different unique flavour of milk which is Café Latte Milk, Premium Chocolate Milk, Dates/Kurma Milk, Strawberries Yogurt Drink, Mango Tango Yogurt Drink and lastly, Mixed Berries Yogurt Drink. The price offered by SyahFresh is reasonable as it follows the fix price for a carton of Farm Fresh Milk that was set by Farm Fresh. With this the customer can enjoy the drink with anytime and anywhere with a smile on their faces.